2023
DOI: 10.3390/ijerph20010892
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Effectiveness of Co-Designed Mental Health Interventions in Primary Care for People Experiencing Homelessness: A Systematic Review

Abstract: People experiencing homelessness (PEH) face a disproportionately high prevalence of adverse mental health outcomes compared with the non-homeless population and are known to utilize primary healthcare services less frequently while seeking help in emergency care facilities. Given that primary health services are more efficient and cost-saving, services with a focus on mental health that are co-designed with the participation of users can tackle this problem. Hence, we aimed to synthesize the current evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…There are other studies that reinforce the links between the provision of a safe environment and the empowerment of participants as enablers for participation when mutual trust, equity, and empathy are embedded in all phases of the research process. Schiffler et al ( 33 ) identified clients were reportedly empowered to achieve their personal goals when co-designed mental health interventions were provided in their living environment, including home, work, and other places that they identified as safe and favourable. Flexibility was perceived as a key element to be applied across the different research's stages as an important strategy to involve people who might otherwise be excluded of participating.…”
Section: Discussionmentioning
confidence: 99%
“…There are other studies that reinforce the links between the provision of a safe environment and the empowerment of participants as enablers for participation when mutual trust, equity, and empathy are embedded in all phases of the research process. Schiffler et al ( 33 ) identified clients were reportedly empowered to achieve their personal goals when co-designed mental health interventions were provided in their living environment, including home, work, and other places that they identified as safe and favourable. Flexibility was perceived as a key element to be applied across the different research's stages as an important strategy to involve people who might otherwise be excluded of participating.…”
Section: Discussionmentioning
confidence: 99%
“…The engagement of stakeholders, that is, 'experts by experience' [54], was a key strength of this study. It is recognised that involving people who are representative of those who might deliver (e.g., local councillors) or receive (e.g., the general public) interventions enhances the likely quality, equity, relevance and long-term sustainability of interventions [55][56][57]. Stakeholders also often possess valuable insights into the specific needs, challenges and preferences of the target population.…”
Section: Strengths Limitations and Future Researchmentioning
confidence: 99%
“…Within the demographic of people impacted by homelessness in the United States, a significant proportion comprises young adults aged between 18 and 24 years old [7]. Available evidence substantiates that homelessness severely affects mental health outcomes [8]. Studies conducted have demonstrated that people experiencing homelessness show higher instances of depression and anxiety than those without housing instability issues [8].…”
Section: Introductionmentioning
confidence: 99%
“…Available evidence substantiates that homelessness severely affects mental health outcomes [8]. Studies conducted have demonstrated that people experiencing homelessness show higher instances of depression and anxiety than those without housing instability issues [8]. Approximately 75% of homeless adults have had at least one form of mental illness before age 25 [7].…”
Section: Introductionmentioning
confidence: 99%